Bladder training prior to urinary catheter removal in total joint arthroplasty. A randomized controlled trial. (January 2019) - Markopoulos, George; Kitridis, Dimitrios; Tsikopoulos, Konstantinos; Georgiannos, Dimitrios; Bisbinas, Ilias
Abstract: Background: Urinary catheters are commonly used in patients undergoing total hip and knee arthroplasty. Bladder training before catheter removal is reported to shorten the time to return to normal bladder function and reduce the incidence of urinary retention. Objective: To evaluate the results of bladder training in patients with total hip and knee arthroplasty. Design: Randomized controlled trial. Setting: Orthopaedic Department of a tertiary Military Hospital. Participants: We enrolled consecutive patients undergoing total hip or knee arthroplasty during a period of 14 months. Methods: We randomly allocated the participants into either a bladder training group, in which clamping was considered prior to catheter removal, or a free drainage removal group, using a computer-generated list and subsequently assessed their need for re-catheterization due to urinary retention. The primary outcome of this study was to evaluate if bladder training in patients with total hip and knee arthroplasty reduces the need for re-catheterization due to urinary retention. Multivariable logistic regression was used to model the association between postoperative urinary retention and independent variables (total hip or total knee arthroplasty, age, gender, and history of diabetes mellitus or prostatism). Secondary outcomes were the incidence of urinary tract infection, and subjective patients' symptoms. Results: We included 218 patients in the study; 114 in the bladder training group and 104 in the free drainage removal group. All patients were over 50 years old with a mean age of 69.3 (SD = 8) years. We observed three cases of urinary retention in the bladder training and six in free drainage removal group, and the difference was not statistically significant (2.6% and 5.8% respectively, p = 0.316). We also observed increased odds of re-catheterization in patients with prostatism under medication (odds ratio was 26.42, p < 0.001). No infections or major subjective symptoms were noted. Conclusion: This trial shows that bladder training by catheter clamping offers no advantage over free draining removal of short-term urinary catheters in patients with total hip and knee arthroplasty. Therefore, we conclude that the bladder training procedure is not indicated. However, healthcare providers should monitor patients' urination after removal of the catheter.